2017
DOI: 10.3382/ps/pex043
|View full text |Cite
|
Sign up to set email alerts
|

The duck enteritis virus early protein, UL13, found in both nucleus and cytoplasm, influences viral replication in cell culture

Abstract: The UL13 protein of the duck enteritis virus (DEV), predicted to encode a Ser/Thr protein kinase, belongs to the family of conserved herpesvirus protein kinases (CHPK), which plays an important role in herpesvirus proliferation. In this study, truncated UL13 was expressed as a fusion protein of approximately 44 kDa using a prokaryotic expression system, and this protein was used to generate a specific anti-UL13 antibody. This antibody detected UL13 starting at 4 h post infection in duck embryonic fibroblast ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…IE genes are expressed in the presence of CHX although the transcription of E and L genes is suppressed [31]. We also treated DEV-infected cells with GCV and examined UL54 (an IE gene) [32], US2 (an L gene) [33], UL13 (an E gene) [34], and β-actin as controls. We found that UL21 gene expression was inhibited in the groups treated with GCV and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…IE genes are expressed in the presence of CHX although the transcription of E and L genes is suppressed [31]. We also treated DEV-infected cells with GCV and examined UL54 (an IE gene) [32], US2 (an L gene) [33], UL13 (an E gene) [34], and β-actin as controls. We found that UL21 gene expression was inhibited in the groups treated with GCV and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…IE genes are expressed in the presence of CHX, though transcription of E and L genes is suppressed (36). We also treated DEV-infected cells with GCV, a DNA polymerase inhibitor, and we examined UL54 (an IE gene) (37), US2 (an L gene) (38), UL13 (an E gene) (39), and β-actin as controls. We found that UL21 gene expression was inhibited in the groups treated with GCV and CHX.…”
Section: Discussionmentioning
confidence: 99%
“…IE genes are expressed in the presence of CHX although the transcription of E and L genes is suppressed (36). We also treated DEV-infected cells with GCV and examined UL54 (an IE gene) (37), US2 (an L gene) (38), UL13 (an E gene) (39), and βactin as controls. We found that UL21 gene expression was inhibited in the groups treated with GCV and CHX.…”
Section: Discussionmentioning
confidence: 99%